Mesin Penumbuk Tepung Mocaf Dengan Sistem Rack And Gear - Muhammad Subhan (Manutech : Jurnal Teknologi Manufaktur, 2019)
Diversification of non-rice food by utilizing existing local food sources, such as corn and tubers, is an effort to maintain food security so that food for the people of Indonesia is reflected in the availability of sufficient food, both in quantity and quality, safe, equitable and affordable. Location-specific non-rice staples can be used as the start of a revival of food diversification in the region, which is ultimately expected to reduce national rice consumption. Policy direction by developing diversification (processing) and consumption of food based on local resources. One of the potentials that can be developed to increase local food potential in Tanah Bawah, is the development of food processing made from cassava. Food products that have been produced by local villagers in the form of mocaf flour and other types of food. During this time, the production process is done manually which requires a lot of manpower and time, so it is less productive. For this reason, it is necessary to design the construction of a pulverization machine by using rack and gear mechanics that can mash the mocaf flour smoothly and evenly in an efficient way. Based on the results of the trial, this machine can mash flour evenly, smooth with a capacity of 5kg/15 minutes.